1997
DOI: 10.1152/ajpregu.1997.273.5.r1709
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-induced depression of rat glucose-6-phosphatase gene expression and activity

Abstract: Sepsis in rats decreases the hepatic expression of the gluconeogenic enzyme glucose-6-phosphatase (G6Pase). The aim of this study was to investigate the relationship among G6Pase transcription, mRNA, enzymatic activity, and serum glucose levels at different intervals during mild or fulminant sepsis. Both fulminant and mild sepsis immediately decreased hepatic G6Pase mRNA levels. In mild sepsis, levels began to recover late in the time course. Serum glucose levels were maintained in mild sepsis but decreased ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 35 publications
7
36
0
Order By: Relevance
“…In addition, blood glucose levels were Ͻ3.0 mmol/L (2.3Ϯ0.2 mmol/L) in LPS-pretreated mice at the initiation of clearance studies compared with Ͼ6.8 mmol/L in vehicle-pretreated mice (8.3Ϯ0.6 mmol/L, PϽ0.001), a finding consistent with severe sepsis. 32 Blood was collected 90 seconds and 1, 2, 3, 4, and 5 hours after injection, and serum levels of Lp(a) were quantified. In vehicle-pretreated mice, serum levels of Lp(a) decreased progressively from 1.09Ϯ0.07 mg/dL at baseline (90 seconds) to 0.41Ϯ0.02 mg/dL after 5 hours, with a half-life of 3.7Ϯ0.2 hours (Figure 2A).…”
Section: Clinical Characteristics Of the 13 Participants At Entry Intmentioning
confidence: 99%
“…In addition, blood glucose levels were Ͻ3.0 mmol/L (2.3Ϯ0.2 mmol/L) in LPS-pretreated mice at the initiation of clearance studies compared with Ͼ6.8 mmol/L in vehicle-pretreated mice (8.3Ϯ0.6 mmol/L, PϽ0.001), a finding consistent with severe sepsis. 32 Blood was collected 90 seconds and 1, 2, 3, 4, and 5 hours after injection, and serum levels of Lp(a) were quantified. In vehicle-pretreated mice, serum levels of Lp(a) decreased progressively from 1.09Ϯ0.07 mg/dL at baseline (90 seconds) to 0.41Ϯ0.02 mg/dL after 5 hours, with a half-life of 3.7Ϯ0.2 hours (Figure 2A).…”
Section: Clinical Characteristics Of the 13 Participants At Entry Intmentioning
confidence: 99%
“…Because hepatic dysfunction is an important but poorly understood component of these disorders, we have investigated changes in hepatic gene expression, structure, and function after cecal ligation and puncture (CLP), a clinically relevant murine model of sepsis (2)(3)(4)(5)(6). Early on, CLP provokes a hyper-inflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of each is reduced shortly after CLP (11). Because sepsis is associated with cholestasis and steatosis (5,8,11), we have postulated that the development of these clinically relevant abnormalities might result from altered expression of these genes (11). Studies by others have implicated several cytokines in the development of cholestasis and steatosis and in the expression of Ntcp, MRP-2, and OATP in response to toxic and anatomical insults (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…47 This has been attributed to the lowered capacity of the liver to supply glucose because of the inhibition of gluconeogenesis as a consequence of the inhibition of the expression of control enzymes of gluconeogenesis and because of the exhaustion of hepatic glycogen pools by proinflammatory cytokines. [10][11][12][13][14][15][16][17][18][19][20][21][22] From the presented results it is concluded that IL-6 and insulin share in part common signal transduction components. This may impair insulin signaling ultimately leading to insulin resistance.…”
Section: Involvement Of Pi3-kinase In the Insulin Inhibition Of Glucamentioning
confidence: 99%
“…Also, in the septic rat, 17,18 in 12-hour TNF-␣-treated mice, 19 and in IL-6-secreting tumor transplanted mice 20 the expression of the gluconeogenic enzyme, glucose-6-phosphatase, was inhibited, which together with the inhibition of PCK gene expression indicates a general impairment of gluconeogenesis by proinflammatory cytokines. In cultured rat hepatocytes 24-hour chronic treatment of hepatocytes with a mixture of IL-1␤, TNF-␣, interferon ␥, and bacterial endotoxin inhibited gluconeogenesis.…”
mentioning
confidence: 97%